A germ cell‐specific ageing pattern in otherwise healthy men. Issue 10 (20th September 2020) - Laurentino, Sandra; Cremers, Jann‐Frederik; Horsthemke, Bernhard; Tüttelmann, Frank; Czeloth, Karen; Zitzmann, Michael; Pohl, Eva; Rahmann, Sven; Schröder, Christopher; Berres, Sven; Redmann, Klaus; Krallmann, Claudia; et al.
Abstract: Life‐long sperm production leads to the assumption that male fecundity remains unchanged throughout life. However, recently it was shown that paternal age has profound consequences for male fertility and offspring health. Paternal age effects are caused by an accumulation of germ cell mutations over time, causing severe congenital diseases. Apart from these well‐described cases, molecular patterns of ageing in germ cells and their impact on DNA integrity have not been studied in detail. In this study, we aimed to assess the effects of 'pure' ageing on male reproductive health and germ cell quality. We assembled a cohort of 198 healthy men (18–84 years) for which end points such as semen and hormone profiles, sexual health and well‐being, and sperm DNA parameters were evaluated. Sperm production and hormonal profiles were maintained at physiological levels over a period of six decades. In contrast, we identified a germ cell‐specific ageing pattern characterized by a steady increase of telomere length in sperm and a sharp increase in sperm DNA instability, particularly after the sixth decade. Importantly, we found sperm DNA methylation changes in 236 regions, mostly nearby genes associated with neuronal development. By in silico analysis, we found that 10 of these regions are located in loci which can potentially escape the first wave of genome‐wide demethylation after fertilization. In conclusion, human male germ cells present a unique germline‐specific ageing process, which likely results in diminished fecundity in elderly men and poorer health prognosis for their offspring. Abstract : In this study we found that healthy ageing in men is associated with a maintenance of normal sperm parameters and hormonal profiles, and maintenance of quality of life. In germ cells, a specific pattern of ageing is found, including increased telomere length, decreased DNA stability, and genome‐wide changes in DNA methylation. These changes to the germ cell genome likely result in diminished fecundity in elderly fathers.